Desquamative interstitial pneumonia: If there is smoke there is fire - Amit Panjwani; Husain Kadhem; Saadeya Naji Abdulkarim; Umesh Nabar (The Journal of Association of Chest Physicians)
Desquamative interstitial pneumonia (DIP) is a rare type of idiopathic interstitial lung disease (ILD) predominantly seen in smokers. Connective tissue diseases (CTDs) are one of the important causes of ILD and may have lung involvement antedating their usual manifestations, making the diagnosis difficult. Interstitial pneumonia with autoimmune features (IPAFs) are ILDs having autoimmune features but not fulfilling the criteria for a definite CTD. A small minority of IPAF cases may progress to CTD–related ILD over a period. Usual interstitial pneumonia (UIP) and nonspecific interstitial pneumonia are common radiological and histopathological patterns associated with IPAF. DIP is a rare manifestation of IPAF. Patients with IPAF and a non-UIP pattern may benefit from immunomodulation. We present a rare case of DIP in a nonsmoker, who was initially labeled as idiopathic ILD but eventually evolved into IPAF and exhibited a good response to immunosuppressive treatment.